Autocrine Human Urotensin II Enhances Macrophage-Derived Foam Cell Formation in Transgenic Rabbits. (12th November 2015) - Zhao, Sihai; Li, Yafeng; Gao, Shoucui; Wang, Xiaojing; Sun, Lijing; Cheng, Daxing; Bai, Liang; Guan, Hua; Wang, Rong; Fan, Jianglin; Liu, Enqi
Abstract : Circulating urotensin II (UII) is involved in the development of atherosclerosis. However, the role of autocrine UII in the development of atherosclerosis remains unclear. Here, we tested the hypothesis that autocrine UII would promote atherosclerosis. Transgenic rabbits were created as a model to study macrophage-specific expressing human UII (hUII) and used to investigate the role of autocrine UII in the development of atherosclerosis. Transgenic rabbits and their nontransgenic littermates were fed a high cholesterol diet to induce atherosclerosis. Comparing the transgenic rabbits with their nontransgenic littermates, it was observed that hUII expression increased the macrophage-positive area in the atherosclerotic lesions by 45% and the positive area ratio by 56% in the transgenic rabbits. Autocrine hUII significantly decreased the smooth muscle cell-positive area ratio in transgenic rabbits (by 54%), without affecting the plasma levels of total cholesterol, triglycerides, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol, and glucose and adipose tissue contents. These results elucidated for the first time that autocrine UII plays an important role in the development of atherosclerosis by increasing the accumulation of macrophage-derived foam cell.